Responsive Feeding: Implications for Policy and Program Implementation(1)(2) - Engle, Patrice L. (American Society for Nutrition, 2011)
In this article, we examine responsive feeding as a nutrition intervention, with an emphasis on the development and incorporation of responsive feeding into policies and programs over the last 2 decades and recommendations for increasing the effectiveness of responsive feeding interventions. A review of policy documents from international agencies and high-income countries reveals that responsive feeding has been incorporated into nutrition policies. Official guidelines from international agencies, nongovernmental organizations, and professional organizations often include best practice recommendations for responsive feeding. Four potential explanations are offered for the rapid development of policies related to responsive feeding that have occurred despite the relatively recent recognition that responsive feeding plays a critical role in child nutrition and growth and the paucity of effectiveness trials to determine strategies to promote responsive feeding. Looking to the future, 3 issues related to program implementation are highlighted: 1) improving intervention specificity relative to responsive feeding; 2) developing protocols that facilitate efficient adaptation of generic guidelines to national contexts and local conditions; and 3) development of program support materials, including training, monitoring, and operational evaluation.